ASSESSMENT OF MANGROVE DIVERSITY, BIOMASS, AND CARBON STOCKS IN THE UJUNGPANGKAH ESTUARY, GRESIK - Fathah, Aulia Lanudia; Semedi, Bambang; Wardana, Fitri Candra; Isdianto, Andik (Directorate of Research and Community Service (DRPM), 2025)
Mangrove ecosystems are recognized as vital blue carbon reservoirs that contribute significantly to climate regulation through biomass-based carbon storage. This study assessed mangrove diversity, structure, biomass, and carbon stocks in two key locations: Banyuurip Mangrove Center (BMC) and Lewean Mangrove Park (LMP), located in the Ujungpangkah Estuary, Gresik. Data were collected from 15 rectangular plots (10 × 10 m) to determine species composition, tree density, Importance Value Index (IVI), above and belowground biomass, and estimated carbon stocks using standard allometric equations. A total of 12 mangrove species were identified, with Avicennia marina emerging as the dominant species in all growth stages across both sites. Tree density varied from 100 to 1,600 trees/ha, reflecting stages of regeneration rather than degradation. The highest IVI values were recorded for A. marina (196.3% in BMC; 146% in LMP). Total biomass and estimated carbon stock were higher in BMC (340.48 Mg/ha; 164.87 Mg C/ha) compared to LMP (125.67 Mg/ha; 56.20 Mg C/ha), primarily due to differences in species dominance and stand maturity. These results underline the ecological and climate mitigation significance of maintaining mangrove diversity and biomass. The study supports the integration of mangrove conservation into blue carbon strategies for sustainable coastal management, and recommends strengthening local restoration initiatives based on dominant species performance.